O razgledu z razglednega stolpa na Mariborskem Pohorju - Žiberna, Igor (Časopis za zgodovino in narodopisje, 2017)
In this treatise, the author discusses the visibility from the lookout tower on Mariborsko Pohorje. Using the photography method, the cartographic materials and with the help of geographic information system the author refutes the theory of Uršlja gora and the Kamnik-Savinja Alps being visible from this lookout tower. The author further on discusses the visibility of the Balaton Lake from the tower. The extreme west part of the lake can be seen under specific meteorological conditions (temperature inversion) and with good atmosphere transparency.
Keywords: daljava obzorja; distant horitons; fizična geografija; GIS; lookout tower; Mariborsko Pohorje; razgledni stolpi; refraction; refrakcija; vidnost; visibility